Ocena sztuki osób z niepełnosprawnością wzroku przez dzieci i dorosłych - SZUBIELSKA, MAGDALENA; PASTERNAK, KATARZYNA; WÓJTOWICZ, MARZENA; SZYMAŃSKA, ANNA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Magdalena Szubielska, Katarzyna Pasternak, Marzena Wójtowicz, Anna Szymańska, Ocena sztuki osób z niepełnosprawnością wzroku przez dzieci i dorosłych [Evaluation of art of people with visual impairment by children and adults]. Interdyscyplinarne Konteksty Pedagogiki Specjalnej, nr 22, Poznań 2018. Pp. 167-183. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.22.10 The aim of the study was to determine whether the age of the audience of the exhibition influences the assessment of aesthetic preferences of artistic products made up by people with visual impairment. The research was conducted to give an answer if there are differences in the preferences of different categories of artworks created by artists who are blind or low vision. The research consisted in the evaluation of raised-line drawings, photographs, sculptures and the tactile picturebook. These artistic products were presented in the art gallery. The assessments were made on a 5-point scale, where the respondents indicated how much they liked the artworks they were watching. In the study participated 118 people, including 80 children and 38 adults. It turned out that age and type of art had an interactive impact on the aesthetic assessment. Age differences in aesthetic preference were found in reference to drawings and picture books. The visual art created by people with sight impairment was evaluated very positively.